Single Coronary Artery Associated with an Arteriovenous Communication: An Incremental Diagnostic Value of Coronary CTA - Touma, Rabih; Singh, Karan T; Kaur, Ramanjit; Mastromatteo, James F; Abidov, Aiden (Journal of Cardiology and Cardiovascular Medicine, 2024)
Single coronary artery and coronary arteriovenous communication are rare congenital cardiac anomalies with potentially harmful effects, making the diagnosis essential for the appropriate management. The coexistence of these two anomalies is exceptional. We present a case illustrating the diagnostic power of Coronary CTA in depicting this unusual combination.